(untitled) (Discourse of Law and Administration, 2025)
The subject of the study is the institution of a complaint against the order of the prosecutor, issued in pre-trial proceedings, on the refusal to give permission to meet with a pretrial detainee in a situation where the application is submitted by the defense counsel. The author analyzes the situation of the defendant’s defense counsel with regard to his procedural rights, in a situation of violation of substantive provisions. It is shown that despite the categorical statement of the norms, a negative decision is possible, which makes it necessary to evaluate the existing appellate system. After presenting the general assumptions of both constitutional and factual nature concerning the introduction of regulations on the restriction of the right to privacy and freedom of communication, the main principles concerning the possibility of obtaining visits and communication by a detainee with third parties are presented. It is shown what, in a historical perspective, premises have shaped the currently functioning institutions. The juxtaposition of the institutions of the right to meeting and the possibility of communication by a temporarily arrested person - in terms of the appeal procedure - was necessary due to the adopted systemic interpretation. On the basis of the analysis of solutions at the linguistic, historical and systemic level, it was shown that there is a system of means of appeal against negative decisions. The arguments presented led to the final conclusion that this system is incomplete. It was established that in the situation of an order to deny a defender to see a detainee on remand, the legislator did not provide for the possibility of filing a complaint against the indicated decision.